Coloration in a Praying Mantis: Color Change, Sexual Color Dimorphism, and Possible Camouflage Strategies - Leah Y. Rosenheim; Jay A. Rosenheim; Michael R. Maxwell (Ecology and Evolution)
ABSTRACT Background matching, an important form of camouflage, can be challenging for animals that range across heterogeneously colored habitats. To remain cryptic in such habitats, animals may employ color change, background choice, or generalist coloration, and the efficacy of these strategies may be influenced by an animal's mobility. We examined camouflage strategies in the praying mantis Stagmomantis limbata. We reared mantids in green or brown containers to test whether mantids change color over development to match their background. Additionally, we tested whether adult mantids (i) employ behavioral background choice, (ii) exhibit sexual color dimorphism, and (iii) differ in mobility in the field. Mantids changed color during development in response to their background, but the effect was small and variable. Adult mantids did not show background choice. In the field, adult males moved greater distances than females. Adults exhibited sexual color dimorphism: Males were heterogeneous in coloration (green body with brown pronotum), while females were more homogeneous in color, ranging continuously from green to brown. We suggest a hypothesis that differences in mobility between the sexes have led to the sexual color dimorphism observed and that this dimorphism reflects different camouflage strategies, with highly mobile males showing a generalist coloration and more sedentary females showing a specialist coloration.